The Values of Multiculturalism in the Qur'an: Perspective of Tafsir An-Nuur - Muhammad Faiz,; Nico Setiawan , (Advances in Humanities and Contemporary Studies, 2025)
A country must have a diversity of ethnicities, cultures, religions and languages, making it a universal nation. If this diversity is not managed properly, it can lead to social conflict. For this reason, values that are able to maintain harmony and unity are needed, one of which is multiculturalism. Tafsir an-Nuur by Hasbi Ash-Shiddieqy is one of the commentaries that has a societal style (adabi ijtima'i) that is relevant in interpreting some verses about diversity. The purpose of this study is to explain the form of interpretation of the values of multiculturalism in the Qur'an from the perspective of tafsir an-Nuur. This research is a type of qualitative research that uses a thematic approach (mauḍu'i), and the main source of this research is the book of tafsir an-Nuur by Hasbi Ash-Shiddieqy. As for data collection or data collected for this research through library research which is then analyzed by content analysis. The results showed that tafsir an-Nuur interpreted a number of verses that contain the values of multiculturalism in it, including  al-Hujurat: 13, ar-Rum: 22, Hud: 118, Ali 'Imran: 64, and surah Yunus: 99. Summarizing Hasbi Ash-Shiddieqy's interpretation in tafsir an-Nuur of these five verses, namely as a form of recognition of social, cultural and religious diversity. In interpreting these verses Hasbi Ash-Shiddieqy also emphasizes that the value of tolerance, religious freedom, interfaith dialogue, and respect for differences is the core of the Qur'anic message.